Fundamentals of air pollution - Boubel, Richard W. (Richard William), 1927-2010 (Academic Press, 1994)
This new edition of the premier air pollution textbook is completely updated and revised to include all components of the 1990 Clean Air Act Amendments. Fundamentals of Air Pollution, Third Edition covers the spectrum of topics pertinent to the study of air pollution: elements, sources, effects, measurement, monitoring, meteorology, and regulatory and engineering control. In addition, the textbook features new chapters on atmospheric emissions from hazardous waste sites, air pathways from hazardous waste sites, and the long-term effects of air pollution on the earth. It also presents updated i.